Monopsony, powerful buyers and small sellers: analysis of Malaysian competition law and lessons learnt from Indonesia - Ahamat, Haniff; Abdul Rahman, Nasarudin; Al Anshori, Milyan Risydan (Inderscience Publishers, 2020)
Powerful buyers have become a problem stifling the market presence of micro, small and medium businesses. Their power in both upstream and downstream markets may allow them to manipulate prices or output. The authors look at whether competition law can address such problem particularly in Malaysia. They use monopsony as the theoretical framework and find that the Malaysian Competition Act 2010 can only be used indirectly against the conduct of powerful buyers due to the lack of express reference to the term monopsony. The existing rules are more often operationalised on the supply side rather than the demand side, making proving the anti-competitive conduct of those buyers difficult. In Indonesia, the main competition legislation i.e. the Law No. 5 of 1999 can be directly used but proving legal violation is also difficult. However, Indonesia has a specific law that protects small sellers from powerful buyers' use of their market power